Application of a sensitive and specific LC‐MS/MS method for determination of eriodictyol‐8‐C‐β‐d‐glucopyranoside in rat plasma for a bioavailability study. (5th June 2014) - Qiu, Feng; Fu, Shujun; Zhang, Xinshi; Gong, Muxin; Wang, Manyuan
Abstract This study is the first to detail the development and validation of a rapid, sensitive and specific LC‐ESI‐MS/MS method for the determination of eriodictyol‐8‐C‐β‐d‐glucopyranoside (EG) in rat plasma. A simple protein precipitation method was used for plasma sample preparation. Chromatographic separation was successfully achieved on an Agilent Zorbax XDB C18 column (2.1 × 50 mm, 3.5 µm) using a step gradient program with the mobile phase of 0.1% formic acid aqueous solution and acetonitrile with 0.1% formic acid. EG and the internal standard (IS) were detected using an electrospray negative ionization mass spectrometry in the multiple reaction monitoring mode. This method demonstrated good linearity and did not show any endogenous interference with the active compound and IS peaks. The lower limit of quantification of EG was 0.20 ng/mL in 50 μL rat plasma. The average recoveries of EG and IS from rat plasma were both above 80%. The inter‐day precisions (relative standard deviation) of EG determined over 5 days were all within 15%. The present method was successfully applied to a quantification and bioavailability study of EG in rats after intravenous and oral administration. The oral absolute bioavailability of EG in rats was estimated to be 7.71 ± 1.52%. Copyright © 2014 John Wiley & Sons, Ltd.